STUDY ABOUT THE INFLUENCE OF THE SAMPLING AND STORAGE CONDITIONS, ON THE RESULT OF THE ANALYSIS OF INSPECTION SAMPLES OF FUNGICIDE MANCOZEB - Fernández Armijos, C. (1998)
The use of pesticides is an important par! of the crop protection system world-wide. In the 1990's, Brazil is not only a pesticide consumer but an importan! pesticidas producer in the southamerican region. The production, marketing and application of pesticidas involve risks to the users and to the environment. Therefore is importan! the quality control of pesticidas at all stages anda close collaboration of all the involved groups. The fungicide Mancozeb has developed problems dueto its breakdown products as Ethylene-thiourea (ETU), which is reported to inhibit the functions of the Thyroid gland, interfering in iodine metabolism. This study appears as a contribution to clarify matters concerning the stability and degradation of ethylenebisdithiocarbamates under different conditions of temperatura, moisture, storage time and sun radiation exposition for a plant protection practice without hazardous side effects.